Carboxylesterase Significant Lower Specific Activity of Meningiomas and Gliomas with Derived Primary Cell Culture Indicate Reduction in Anticancer Drug Metabolism - Prabha Muddobalaiah; Vasanthapuram Ravi; Narayana Swamy Ramachandra Swamy (Pharmaceutical Research: Recent Advances and Trends Vol. 6, 2024)
Aims: Carboxylesterases (CE) convert carboxylic esters to alcohols and carboxylic acids. CE is a protective factor in the brain cells categorized as phase-I drug-metabolizing enzymes. Therefore, our objective is to find out the different CE-specific activity of brain tumors as compared to the normal brain to understand the drug metabolism efficiency. Background: Carboxylesterase activity can be influenced by interactions of a variety of compounds either directly or at the level of enzyme regulation. For e.g. drug elimination decreases and the incidence of drug-drug interactions increases when two or more drugs compete for hydrolysis by the same carboxylesterase isozyme. Materials and Methods: Total Protein and Carboxylesterase assays were performed for Meningiomas and gliomas and derived primary cell culture. CE spectrophotometric assays were studied for 30 meningiomas and 52 gliomas in 82 males, while 45 meningiomas and 29 gliomas in 74 female patients and derived cell culture respectively. The brain tumor protein band pattern was studied by electrophoresis. Results: The brain tissue extracts for SDS PAGE displayed a highly intense single protein (not purified) band of 60 KDa in brain tumors as compared to normal brains. The similar CE-specific activity exhibited between the meningiomas 20.96±5.071 (n=50) and gliomas 20.77±4.4644 nmol/min/mg (n=61) respectively showed significantly lower CE activity as compared to normal Brain (n=106) 52.355 ± 11.15 nmol/min/mg of protein and p-value was less than 0.0001 extremely statistically significant. Hence CE activities are significantly lower in all grades of parent Brain tumors as compared to normal brains. Primary cell cultures with respective passages expressed lower CE activities than parent tumors respectively. CE activity has to be determined for meningiomas by comparing them with meninges to understand the efficiency of drug metabolism. Hence Carboxyl esterase can also be made as biomarkers by developing kits for diagnosis purposes. Thus the current study promotes applications in the future by determining tumor and cell culture CE-specific activity for designing anticancer drugs for efficient metabolism and Targeting. Conclusions: The current results indicate the reason for the failure of anticancer drug metabolism efficiency due to lower CE- specific activity in both meningiomas and gliomas respectively. Advanced molecular biochemistry and neuropharmacology benefit from the current study’s ability to solve the drug metabolism problem in order to effectively design drug conjugates for anticancer drug metabolism by CE-specific activity and to monitor chemotherapy for anticancer drug therapeutics for future clinical applications.